2011
DOI: 10.1038/bjc.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Different miRNA signatures of oral and pharyngeal squamous cell carcinomas: a prospective translational study

Abstract: Background:MicroRNAs (miRNAs) are small non-coding RNAs, which regulate mRNA translation/decay, and may serve as biomarkers. We characterised the expression of miRNAs in clinically sampled oral and pharyngeal squamous cell carcinoma (OSCC and PSCC) and described the influence of human papilloma virus (HPV).Methods:Biopsies obtained from 51 patients with OSCC/PSCC and 40 control patients were used for microarray analysis. The results were correlated to clinical data and HPV status. Supervised learning by suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
181
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(202 citation statements)
references
References 41 publications
17
181
2
2
Order By: Relevance
“…Gain-of-function experiments in lung cancer cell lines have shown that miRNA 125a-5p suppressed proliferation and induced apoptosis (15). In HNSCC, miRNA 125a-5p did not change (18) or was reduced regarding human papillomavirus (HPV)-positive tumors (19). In the present study, JA is shown to be one of numerous neoplasms that exhibit downregulated miRNA 125a-5p.…”
Section: Discussionmentioning
confidence: 67%
“…Gain-of-function experiments in lung cancer cell lines have shown that miRNA 125a-5p suppressed proliferation and induced apoptosis (15). In HNSCC, miRNA 125a-5p did not change (18) or was reduced regarding human papillomavirus (HPV)-positive tumors (19). In the present study, JA is shown to be one of numerous neoplasms that exhibit downregulated miRNA 125a-5p.…”
Section: Discussionmentioning
confidence: 67%
“…The results varied, with many miRs proposed to correlate with tumor HPV status or outcome, with few miRs found common between studies. Mir-9, 155 and 163b were in several studies found overexpressed in HPV-positive vs. HPV-negative OPSCC, while miR-31 and 193b were downregulated (68)(69)(70)(71)73). Also, a 25 miR signature discriminating HPV-positive vs. HPV-negative OPSCC was suggested, but few of the indicated miRs were common with other studies (67).…”
Section: Microrna Expression In Oropharyngeal Cancer In Relation To Hmentioning
confidence: 91%
“…MicroRNA (miR) expression in OPSCC has been mainly analyzed in normal tissue, HPV-positive vs. HPV-negative tumor status and to a lesser extent to outcome (67)(68)(69)(70)(71)(72)(73). The results varied, with many miRs proposed to correlate with tumor HPV status or outcome, with few miRs found common between studies.…”
Section: Microrna Expression In Oropharyngeal Cancer In Relation To Hmentioning
confidence: 99%
“…In this review, we have listed nine miRNA expression signatures in HNSCC and ESCC. 12,13,15, [18][19][20][21][22][23] Differentially expressed miRNAs are summarized based on the nine signatures in Table 1. Recently, we conducted miRNA expression signature analyses in hypopharyngeal-SCC, maxillary sinus SCC and ESCC using clinical specimens.…”
Section: Aberrant Expression and Functional Significance Of Mir-375 Imentioning
confidence: 99%
“…16,17 Other research groups also showed downregulation of miR-375 in HNSCC and ESCC and other types of human cancers. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] In this review, we focus on HNSCC and ESCC and describe the aberrant expression of miRNAs in these cancers and the cancer pathways they may regulate in these diseases.…”
Section: Introductionmentioning
confidence: 99%